Multilevel subdural and epidural hematoma after percutaneous kyphoplasty (PKP): a case report and literature review - Fuyuan Deng; Hailong Liu (Frontiers in Medicine)
BackgroundSerious complications such as intraspinal hematoma after percutaneous kyphoplasty (PKP) are rare, with an incidence of about 1%, which has been reported in relevant literature. However, there are few reports on the simultaneous occurrence of multiple segmental subdural/epidural hematomas (SDH/SEH) after surgery.Case presentationThis case reports a 90-year-old female with lower limb neurological dysfunction after PKP. Emergency thoracolumbar magnetic resonance imaging (MRI) showed hematoma compressing the spinal cord. After conservative treatment, the sensory and motor function of the right lower limb returned to normal, and the bowel and urine function returned to normal, but the muscle strength of the left lower limb did not fully recover.ConclusionBlood pressure should be well controlled during the perioperative period for elderly patients with hypertension. This will avoid severe fluctuations in blood pressure caused by pain, anesthesia, and other reasons, reduce the probability of intraspinal vascular rupture, and prevent severe neurological dysfunction caused by acute intraspinal hemorrhage.